2002
DOI: 10.1098/rspb.2002.2197
|View full text |Cite
|
Sign up to set email alerts
|

Space and the persistence of male–killing endosymbionts in insect populations

Abstract: Male-killing bacteria are bacteria that are transmitted vertically through the females of their insect hosts. They can distort the sex ratio of their hosts by killing infected male offspring. In nature, male-killing endosymbionts (male killers) often have a 100% efficient vertical transmission, and multiple male-killing bacteria infecting a single population are observed. We use different model formalisms to study these observations. In mean-field models a male killer with perfect transmission drives the host … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 27 publications
4
34
0
Order By: Relevance
“…R. Soc. B 282: 20152068 efficacy and a benefit provided to the surviving host offspring by killing the infected male embryos [10], and may also depend on their spatial distribution [11]. We showed that a purely vertically transmitted non-MK bacterium, otherwise able to invade the host as a highly efficient male-killer (electronic supplementary material, appendix S3), cannot persist and evolve MK gradually unless at least a bit of HT is present.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…R. Soc. B 282: 20152068 efficacy and a benefit provided to the surviving host offspring by killing the infected male embryos [10], and may also depend on their spatial distribution [11]. We showed that a purely vertically transmitted non-MK bacterium, otherwise able to invade the host as a highly efficient male-killer (electronic supplementary material, appendix S3), cannot persist and evolve MK gradually unless at least a bit of HT is present.…”
Section: Discussionmentioning
confidence: 98%
“…In fact, the presence of HT in MK bacteria could explain the existence of perfectly vertically transmitted male-killers in the field [24]. In spatial models, a perfectly vertically transmitted male-killer can both invade and persist in a host [11]. In the absence of any spatial component, the male-killer drives the population to extinction [10,25,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The only study [28] that explicitly addressed the persistence of male killing endosymbionts and infection prevalence within a spatial setting confirmed the importance of colonization-extinction dynamics, although at the local scale (i.e. within in a population).…”
Section: Discussionmentioning
confidence: 99%
“…The GGH has been continuously and successfully applied to model biological and biomedical processes, including Tumor growth (Dormann et al , 2001; dos Reis et al , 2003; Drasdo et al , 2003; Holm et al , 1991; Turner and Sherratt, 2002), Gastrulation (Drasdo and Forgacs, 2000; Drasdo et al , 1995; Longo et al , 2004), Skin pigmentation (Collier et al , 1996; Honda et al , 2002; Wearing et al , 2000), Neurospheres (Zhdanov and Kasemo, 2004a,b), Angiogenesis (Ambrosi et al , 2004; Ambrosi et al , 2005; Gamba et al ., 2003; Merks et al ., 2008; Merks and Glazier, 2006; Murray, 2003; Pierce et al ., 2004; Serini et al ., 2003), the Immune system (Kesmir and de Boer, 2003; Meyer-Hermann et al ., 2001), Yeast colony growth (Nguyen et al ., 2004; Walther et al ., 2004), Myxobacteria (Alber et al ., 2006; Arlotti et al ., 2004; Börner et al ., 2002; Bussemaker et al ., 1997; Dormann et al ., 2001), Stem cell differentiation (Knewitz and Mombach, 2006; Zhdanov and Kasemo, 2004a,b), Dictyostelium discoideum (Marée and Hogeweg, 2001, 2002; Marée et al ., 1999a,b; Savill and Hogeweg, 1997), Simulated evolution (Groenenboom and Hogeweg, 2002; Groenenboom et al ., 2005; Hogeweg, 2000; Johnston, 1998; Kesmir et al ., 2003; Pagie and Mochizuki, 2002), General developmental patterning (Honda and Mochizuki, 2002; Zhang et al , 2011), Convergent extension (Zajac, 2002; Zajac et al , 2002; Zajac et al ., 2003), Epidermal formation (Savill and Sherratt, 2003) Hydra regeneration (Mombach et al ., 2001; Rieu et al ., 2000), Plant growth , (Grieneisen et al ., 2007), Retinal patterning (Mochizuki, 2002; Takesue et al , 1998), Wound healing (Dallon et al , 2000; Maini et al ., 2002; Savill and Sherratt, 2003), Biofilms (Kreft et al ., 2001; Picioreanu et al ., 2001; Poplawski et al ., 2008; Van Loosdrecht et al ., 2002), Limb bud development (Chaturvedi et al ., 2004; Poplawski et al ., 2007), somite segmentation (Glazier et al ., 2008; Hester et al , 2011), vascular system development (Merks and Glazier, 2006), choroidal neovascularization, lumen formation, cellular intercalation (Zajac et al ., 2000, 2003), etc. ….…”
Section: Glazier-graner-hogeweg (Ggh)modelingmentioning
confidence: 99%